Influence of multiple freezing/thawing cycles on a structural, rheological, and textural profile of fermented and unfermented corn dough. Issue 11 (13th October 2019) - Yaqoob, Sanabil; Liu, Huimin; Zhao, Chengbin; Liu, Meihong; Cai, Dan; Liu, Jingsheng
Abstract: In the current study, the impact of fermentation and freezing/thawing treatment on corn flour was studied. Fermentation revealed an increase (12%) in amylose content, while freezing reflected a loss of amylose. The results of scanning electron microscope (SEM) revealed more grooves, indentations, and the irregular shape of particles. Rapid Visco Analyzer (RVA) exhibited different pasting behavior on the dough. The molecular structure had similar profiles but showed several discernible absorbance at the different wavelengths. Differential scanning calorimetry (DSC) showed an increase in melting temperature range due to fermentation and freezing/thawing treatment attributed to more heterogeneous morphology. Overall, the results of this research showed the insight alterations that induce the changes in corn flour leading to improvement in some properties and it may enhance the acquaintance about the upright revolution in the profile of corn dough and its potential usage in industry and homes. Abstract : Fermentation and multiple freezing/ thawing treatment modified the dough quality and has better applicability. These modifications exerted a positive impact on physicochemical, structural, rheological, morphological, and thermal properties of corn dough. Freezing interferes with the overall profile of dough due to pressure exerted by ice crystals and due to phase transformation and leaching of constituents such as protein, starch, and lipids.